A cost minimization analysis of intracameral cefuroxime and moxifloxacin in cataract surgery (Annals of Medical Research, 2021)
Aim: In this study, we aim to perform Cost Minimization Analysis of cefuroxime and moxifloxacin, which have proven to have a similar efficacy in the prophylaxis of endophthalmitis after cataract surgery.Material and Methods: The records of 1097 patients who had undergone cataract surgery and intracameral antibiotic (cefuroxime, moxifloxacin) injection in 2018 were evaluated retrospectively. Patients undergoing cataract surgery were divided into two groups according to the type of antibiotic injected into the anterior chamber. Group 1 consisted of patients who received intracameral 1mg/0.1ml cefuroxime and Group 2 consisted of patients who received intracameral 500 µg /0.1ml moxifloxacin. In the postoperative period, patients in both groups received topical antibiotic drops containing 0.5% moxifloxacin and steroid drops containing 0.1% dexamethasone for 7 days. Results: The Group 1 consisted of 213 (19.4%) patients, of which 97 (45.5%) were male and 116 (54.5%) were female, while Group 2 consisted of 884 (80.6) patients, of which 439 (49.7%) were male, and 445 (50.3%) were female (p=0.280). The groups were similar in terms of age and gender distribution of the patients. There was no significant difference in terms of the posterior capsule rupture development between the two groups (p=0.692).BCVA was statistically significant before and after surgery in both groups. None of the patients in both groups developed endophthalmitis. The cost of the drugs used in the first group was 3 times higher than the second group.Conclusion: The antibiotics injected to the anterior chamber during cataract surgery have similar effectiveness, moxifloxacin injection to the anterior chamber was found to be more advantageous in terms of cost, compared to the use of disposable cefuroxime.Keywords: Cataract surgery; intracameral antibiotic; cost.
Keywords: Cataract surgery; intracameral antibiotic; cost.